Hipoalbuminemia sebagai prediktor mortalitas pada pasien Covid-19: Studi kasus di RSUD Prof. Dr Margono Soekarjo Purwokerto - Chasanah, Imah Nur; Sri Rejeki, Dwi Sarwani; Mars Wijayanti, Siwi Pramatama (Poltekkes Kemenkes Aceh, 2024)
Background: Mortality in COVID-19 patients is related to several factors, including comorbidities, age, gender, increased D-dimer levels, elevated CRP levels, lymphopenia, leukocytosis, and hypoalbuminemia. Nevertheless, there is a scarcity of research on the impact of hypoalbuminemia on COVID-19 mortality, particularly in Indonesia.Objective: This study aimed to determine the effect of hypoalbuminemia, age, gender, and comorbid status on the mortality rate of COVID-19 patients at Prof. Dr. Margono Soekarjo Hospital.Methods: This research employed an observational analytic method, utilising a cohort design and survival analysis approach. The study was conducted at Prof. Dr. Margono Soekarjo Purwokerto Hospital in December 2023. The study utilised September 2021 medical records as secondary data. The data was analysed using Cox regression to determine the hazard ratio value. The results were deemed statistically significant if the p-value was < 0,05.Results: In September 2021, 217 individuals were hospitalised due to COVID-19. Out of all the patients, only 119 satisfied the specific criteria to be considered as study samples. A total of 49,6% of patients suffered from hypoalbuminemia. The mortality rate was 27,73%, with a higher incidence observed in patients with hypoalbuminemia (25 cases) compared to those without hypoalbuminemia (8 cases). The multivariate analysis revealed that patients with hypoalbuminemia had a 1,8-fold increased risk of mortality compared to patients without hypoalbuminemia (p = 0,007). The age (p = 0,08), gender (p = 0,38), and comorbid status (p = 0,22) of COVID-19 patients did not significantly affect mortality.Conclusion: COVID-19 patients with hypoalbuminemia had a 1,8-fold increased risk of mortality compared to those without hypoalbuminemia. Therefore, it can be inferred that hypoalbuminemia may serve as a prognostic indicator of mortality in COVID-19 patients. KeywordsAlbumin, COVID-19, death, hypoalbuminemia